2018
DOI: 10.3390/sports6020042
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sleep Extension on Sleep, Performance, Immunity and Physical Stress in Rugby Players

Abstract: (1) Background: The purpose of the present study was to examine the efficacy of sleep extension in professional rugby players. The aims were to: (i) characterise sleep quantity in elite rugby players and determine changes in immune function and stress hormone secretion during a pre-season training programme; (ii) evaluate the efficacy of a sleep extension intervention in improving sleep, markers of physical stress, immune function and performance. (2) Methods: Twenty five highly trained athletes from a profess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 36 publications
5
60
1
Order By: Relevance
“…The daily cares combined with sleep management improved the cognitive capacity assessed through sustained attention as number of lapses were significantly lower at T2, T3 and T4 (compared to T0 and T1), and remained lower after week-end at home (T5) and after three days of consecutive work (T6). Adding night-time sleep opportunity (sleep intervention) was previously shown effective in improving alertness and performance in sustained attention using the PVT test in short sleeper workers [19,35]. Our results are the first to show that hydrotherapy cares have a beneficial effect on the sustained attention the very next day, which persisted the week after leaving the resort, while the TST returned to the baseline level.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The daily cares combined with sleep management improved the cognitive capacity assessed through sustained attention as number of lapses were significantly lower at T2, T3 and T4 (compared to T0 and T1), and remained lower after week-end at home (T5) and after three days of consecutive work (T6). Adding night-time sleep opportunity (sleep intervention) was previously shown effective in improving alertness and performance in sustained attention using the PVT test in short sleeper workers [19,35]. Our results are the first to show that hydrotherapy cares have a beneficial effect on the sustained attention the very next day, which persisted the week after leaving the resort, while the TST returned to the baseline level.…”
Section: Discussionsupporting
confidence: 54%
“…This chronic sleep debt and repeated sleep/wake cycle disturbances induced behavioral changes (diurnal sleepiness, anxiety, fatigue) and impairments of cognitive and physical capacities (decreases of sustained attention and physical capacity, increase of mistakes, fatigue, pain, etc) [17,18]. Implementing a sleep extension programme was recently shown to improve sleep and sustained attention with beneficial changes in stress hormone expression among professional athletes [19].…”
Section: Journal Of Sleep Disorders and Therapymentioning
confidence: 99%
“…A decrease in sleep efficiency was strongly associated with an increase in hyperarousal scores ( r =−0.611). Furthermore, a study by Swinburne et al 47 examined the effect of a sleep extension period on sleep, performance, immunity, and stress in rugby players. Results indicated improved sleep indices, and beneficial changes in cortisol expression and reaction time performance.…”
Section: Physiology Of Sleep For Athletesmentioning
confidence: 99%
“…Sleep sufficiency depends on components of quality, quantity, and timing of the sleep window [9]. Research has shown benefits of optimized sleep for athletic performance [10][11][12]. Even so, knowledge regarding the sleep behaviors of athletes is limited [13,14].…”
Section: Introductionmentioning
confidence: 99%